Evaluation of crack-tip fields from DIC data: A parametric study. (August 2016) - Mokhtarishirazabad, M.; Lopez-Crespo, P.; Moreno, B.; Lopez-Moreno, A.; Zanganeh, M.
Abstract: In the past two decades, crack-tip mechanics has been studied increasingly using full-field techniques. Within these techniques, Digital Image Correlation (DIC) has been most widely used due to its many advantages, to extract important crack-tip information, including Stress Intensity Factor (SIF), crack opening displacement, J-integral, T-stress, closure level, plastic zone size, etc. However, little information is given in the literature about the experimental setup that provides best estimations for the different parameters. The current work aims at understanding how the experimental conditions used in DIC influence the crack-tip information extracted experimentally. The influence of parameters such as magnification factor, the position of the images with respect the crack-tip and size of the subset used in the correlation is studied. The influence is studied in terms of SIF by using Williams' model. In this regard, cyclic loading on a fatigue crack in a compact tension (CT) specimen, made of aluminium 2024-T351 alloy, has been applied and the surface deformation around the crack-tip has been examined. The comparison between nominal and experimental values of K I showed that the effect of subset size on the measured K I is negligible compared to the effect of the field of view and the position of the area of interest.